If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(u + -9) = -54 Reorder the terms: 3(-9 + u) = -54 (-9 * 3 + u * 3) = -54 (-27 + 3u) = -54 Solving -27 + 3u = -54 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 3u = -54 + 27 Combine like terms: -27 + 27 = 0 0 + 3u = -54 + 27 3u = -54 + 27 Combine like terms: -54 + 27 = -27 3u = -27 Divide each side by '3'. u = -9 Simplifying u = -9
| (3x×sinx)/2x=sin40 | | -2(y+4)+4(2y+5)= | | 7(x+2)-6= | | 4n=2*12 | | x^2+y^2=3x-4y | | -3(y+5)-2y= | | 20=-5/2u | | -(x+1)-1= | | -(-y-4w+3)= | | (3y)=x-2x | | -5(-1)(-3)(-3)= | | 6(11-2)=54 | | P+9=56 | | 7+3*x=31 | | P+a=56 | | (3y)=x-2xsquared | | P+a=55 | | 5n-10=37 | | X=63-x/0.4 | | -3+(N+1)=12 | | wn2/3w=5/8 | | Log(9x+7)=1 | | (h+9)=2x-6 | | N+[4-2(3-5)]=6 | | bj=104 | | -17+a=-(-10) | | 1=3.5t | | 0.75(12x+8)=2x-15 | | .19*.23=x | | .19*.23= | | 2x-5=27-6x | | 3(u+3)-7u=37 |